2017
DOI: 10.2166/ws.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of different watershed management scenarios developed by simulation–optimization model

Abstract: The effort to control sediment yield at watershed scale is an ongoing challenge that needs to take into account trade-offs between two conflicting objective functions, i.e. economic and hydrologic criteria. Therefore, researchers have coupled hydrologic and multi-objective optimization models to find Pareto-optimal solutions. However, very limited studies have been conducted to analyse the cost-effectiveness (C/E) of scenarios obtained in the Pareto-front optimal. This could provide new information leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Site-specific conditions and dimensions of agricultural BMPs as well as the tillage practices can be incorporated in the SWAT model which is often beyond the capacity of most other watershed models (Xie et al, 2015). The effectiveness of BMPs using the SWAT model has been explored by researchers worldwide (McGregor et al, 1999;Pandey et al, 2005Pandey et al, , 2009b; Betrie et al, 2011;Zhang and Zhang, 2011;Bossa et al, 2012;Strauch et al, 2013;Rocha et al, 2015;Pare et al, 2015;Lampurlanes et al, 2016;Maharjan et al, 2016;Strehmel et al, 2016;Her et al, 2017;Noor et al, 2017;Merriman et al, 2018;Ni and Parajuli, 2018;Qiu et al, 2018;Wang et al, 2018). These studies revealed that the SWAT model has the ability to evaluate BMPs to reduce NPS pollution (sediment and nutrient load) depending on watershed characteristics, and the type and combinations of applied BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific conditions and dimensions of agricultural BMPs as well as the tillage practices can be incorporated in the SWAT model which is often beyond the capacity of most other watershed models (Xie et al, 2015). The effectiveness of BMPs using the SWAT model has been explored by researchers worldwide (McGregor et al, 1999;Pandey et al, 2005Pandey et al, , 2009b; Betrie et al, 2011;Zhang and Zhang, 2011;Bossa et al, 2012;Strauch et al, 2013;Rocha et al, 2015;Pare et al, 2015;Lampurlanes et al, 2016;Maharjan et al, 2016;Strehmel et al, 2016;Her et al, 2017;Noor et al, 2017;Merriman et al, 2018;Ni and Parajuli, 2018;Qiu et al, 2018;Wang et al, 2018). These studies revealed that the SWAT model has the ability to evaluate BMPs to reduce NPS pollution (sediment and nutrient load) depending on watershed characteristics, and the type and combinations of applied BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although few recent studies have shown that the cost-effectiveness of BMPs in mitigating pollution is greatly boosted by using BMP selection and placement tool at watershedscale [32,33], studies which incorporate hotspots and fund limitations, not only for sediment and nutrient load reduction, but also for Atrazine and E. coli, are rare. Thus, based on the financial constraint of $500,000 annually for three years of the NWQI, and the detailed preliminary assessment conducted by the NDEE, the objectives of this study are to: (i) simulate BMPs proposed by the NDEE within target sub-watersheds to determine reductions in pollutant loads and (ii) determine if water-quality standards are met at the watershed outlet.…”
Section: Introductionmentioning
confidence: 99%